Information and Communication Technology in the Learning Process - Azis, Abdul; Nurasiah; Teuku Kusnafizal; Sakdiyah; Alfian (JTP - Jurnal Teknologi Pendidikan, 2024)
During the COVID-19 pandemic, the Indonesian Government issued a policy to implement Distance Learning (PJJ) or Online Learning. This applies to all levels of education, elementary, junior high, high school and university. During online learning, students are not only required to have learning independence but also self-regulation and social support to meet the expected learning outcomes. This study aims to describe the utilization of information and communication technology in learning history class X SMA Negeri 1 Banda Aceh. This research uses qualitative research methods with a case study approach. Data collection in this study used observation, interview, questionnaire, and document methods to obtain data on the utilization of information and communication technology in history learning. The results showed that: first, the utilization of information and communication technology in the history learning process of class has been implemented well. Second, there are advantages in the use of information and communication technology during the history learning process in the COVID-19 era, namely: (1) more flexible schedule; (2) easier assessment; (3) students do not need to go to school; (4) parents can accompany students during the learning process, and (5) students can access the internet to answer questions given by the teacher.